Effect of Turmeric Rhizome Powder on Performance and Carcass Characteristics of Broiler Chickens - Emadi, M.; Kermanshahi, H. (International Journal of Poultry Science, 2006)
In order to study the effect of turmeric rhizome powder (TRP) on performance and carcass characteristics of broiler chickens, an in vivo experiment was conducted. A corn- soybean meal based diet containing levels of TRP (0.00, 0.25, 0.50 and 0.75%) was used. In a completely randomized design with four treatments of five replicates each, and 10 chickens per replicate, 200, Ross male broiler chickens from 0-49 days were studied. For performance, feed intake and body weight gain recorded weekly. For carcass characteristics, at the end of experiment at 49 days of age, one chicken from each replicate of treatments were weighed, slaughtered and the relative weight of liver, pancreas, spleen, heart and abdominal fat pad measured. By Roche colour fan, skin colour was also measured. In all weeks the amounts of feed intake, weight gain and feed to gain ratio in broilers fed treatments were not significantly different. Addition of TRP into the diets significantly (P< 0.05) decreased relative abdominal fat pad and heart weights to live body weight. Under the conditions of this experiment, it was concluded that TRP may improve carcass quality and leaner meat would be predictable. Use of TRP as a reducing heart weight factor, may show some improve in circulatory and respiratory systems that needs to be clarified.